Kemampuan Komunikasi Interpersonal Dosen Dalam Meningkatkan Kemandirian Belajar Mahasiswa - Hamandia, Muhammad Randicha (Jurnal Publisitas, 2020)
Learning is a process of changing behaviour towards a better direction. In the learning process, individual needs independence in order to achieve effective and efficient learning goals. But in this case, there are still students get the problem in the learning independence.The goals of this research is to find out how the interpersonal communication skills of lecturers in increasing of learning independence to the student in broadcasting islamic communication program in communication and dakwah faculty, State islamic University of Raden Fatah Palembang. The method are used in this research namely qualitative. Data collection techniques in this study are interviews and observations. In this case researcher use qualitative descriptive data analysis techniques. The result of this research includes: (1)interpersonal communication skills which apllied by lecturers to increase students learning independence which including, (a)openness, (b) empathy, (c)supportive attitude, (d)positive attitude and also(equality); and (2)The learning independence of the students of islamic broadcasting communication program, dakwah faculty of communication in state islamic university raden fatah palembang has gotten the increasing to many aspects (a)confidence, (b)learning activeness, (c) discipline in learning, and (d) responsible in learning.